Current Evidence on Local Therapies in Advanced Adrenocortical Carcinoma - Kimpel, Otilia; Dischinger, Ulrich; Altieri, Barbara; Fuss, Carmina Teresa; Polat, Bülent; Kickuth, Ralph; Kroiss, Matthias; Fassnacht, Martin (Hormone and Metabolic Research, 2024)
International guidelines emphasise the role of local therapies (LT) for the treatment of advanced adrenocortical carcinoma (ACC). However, large studies are lacking in this field. Therefore, we performed a review of the literature to synthesise current evidence and develop clinical guidance. PubMed database was searched for systematic literature. We identified 119 potentially relevant articles, of which 21 could be included in our final analysis. All were retrospective and reported on 374 patients treated with LT for advanced ACC (12 studies on radiotherapy, 3 on transarterial chemoembolisation and radioembolisation, 4 on image-guided thermal ablation [radiofrequency, microwave ablation, and cryoablation, and two studies reporting treatment with several different LT]). Radiotherapy was frequently performed with palliative intention. However, in most patients, disease control and with higher dosage also partial responses could be achieved. Data for other LT were more limited, but also point towards local disease control in a significant percentage of patients. Very few studies tried to identify factors that are predictive on response. Patients with a disease-free interval after primary surgery of more than 9 months and lesions<5 cm might benefit most. Underreporting of toxicities may be prevalent, but LT appear to be relatively safe overall. Available evidence on LT for ACC is limited. LT appears to be safe and effective in cases with limited disease and should be considered depending on local expertise in a multidisciplinary team discussion.
Keywords: adrenal cancer; advanced disease; local therapies